Pendampingan Pengelolaan Keuangan Untuk Meningkatkan Kinerja Bisnis Homestay di Desa Wisata Bantaragung - Metha Dwi Apriyanti; Andi Kusuma Negara; Lena Erdawati; Dede Sunaryo; Abdul Karim (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service program aimed to improve the financial management capacity of homestay owners through mentoring activities focused on simple bookkeeping, preparation of financial statements, operational cost calculation, pricing strategies, and business feasibility analysis. The program applied the Asset-Based Community Development (ABCD) approach by utilizing local community potential through participatory training, mentoring, discussion, and evaluation. The mentoring results showed an improvement in participants' understanding and skills in recording financial transactions, preparing cash flow and profit-loss reports, identifying operational costs, determining reasonable room rates, and evaluating business performance using financial indicators. The program also encouraged participants to separate personal and business finances and implement simple financial management practices to support business sustainability. The mentoring activities are expected to strengthen the financial resilience of homestay businesses while supporting the sustainable development of Bantaragung Tourism Village.